Whatsapp Business As Customer Relationship Management Media - Fitri Wahyu Rahmadania; Nurhidayat Nurhidayat (Peneliti.net, 2023)
The covid-19 pandemic hit Indonesia which forced many businesses in every sector to close their operations temporarily as the government imposed social and physical distance regulations to stop the outbreak. At the beginning of the pandemic, many businesses were struggling to make ends meet since the stores had to be closed and the customers had to stay at home. PT. Gramedia was one of the businesses that face not only in terms of sales volume but also about how to maintain the customer’s loyalty. By adopting whatsapp business as their customer relationship management media, the company could operate safely according to the health regulations which relate to the customer’s transactions as well as maintain their loyalty. Whatsapp business has created an opportunity for the company to inform, engage and manage customer relationships without any limitations. The research aims to understand how to use whatsapp business as customer relationship management media in maintaining the customer’s loyalty of PT. Gramedia during the covid-19 pandemic. With the features of this new media platform, the research could analyze how the company uses them in order to maintain the customer’s loyalty. The research used the qualitative method by collecting data through in-depth-interviews, non-participant observations, and literature reviews which were associated with research object. The findings showed that how PT. Gramedia implements various customer relationship management strategies, especially utilizing features of whatsapp business to maintain the customer’s loyalty during the covid-19 pandemic.